On Adjacency Spectrum of Non-Zero Divisor Graph of \(\mathbb{Z}_n\) - Babariya, S. K.; Lalchandani, P. T. (Communications in Mathematics and Applications, 2025)
In this article, utilizing the concept of the \(H\)-generalized join graph, we derive the adjacency spectrum of \(Φ(\mathbb{Z}_{p^k})\), where \(p\) be a prime and \(k ≥ 1\) is a positive integer.